In Situ Carbon Corrosion and Cu Leaching as a Strategy for Boosting Oxygen Evolution Reaction in Multimetal Electrocatalysts. Issue 13 (17th February 2022) - Zhang, Jian; Quast, Thomas; He, Wenhui; Dieckhöfer, Stefan; Junqueira, João R. C.; Öhl, Denis; Wilde, Patrick; Jambrec, Daliborka; Chen, Yen‐Ting; Schuhmann, Wolfgang
Abstract: The number of active sites and their intrinsic activity are key factors in designing high‐performance catalysts for the oxygen evolution reaction (OER). The synthesis, properties, and in‐depth characterization of a homogeneous CoNiFeCu catalyst are reported, demonstrating that multimetal synergistic effects improve the OER kinetics and the intrinsic activity. In situ carbon corrosion and Cu leaching during the OER lead to an enhanced electrochemically active surface area, providing favorable conditions for improved electronic interaction between the constituent metals. After activation, the catalyst exhibits excellent activity with a low overpotential of 291.5 ± 0.5 mV at 10 mA cm −2 and a Tafel slope of 43.9 mV dec −1 . It shows superior stability compared to RuO2 in 1 m KOH, which is even preserved for 120 h at 500 mA cm −2 in 7 m KOH at 50 °C. Single particles of this CoNiFeCu after their placement on nanoelectrodes combined with identical location transmission electron microscopy before and after applying cyclic voltammetry are investigated. The improved catalytic performance is due to surface carbon corrosion and Cu leaching. The proposed catalyst design strategy combined with the unique single‐nanoparticle technique contributes to the development and characterization of high‐performance catalysts for electrochemical energy conversion. Abstract : In situ carbon corrosion and Cu leaching during the oxygen evolution reaction (OER) in multimetal electrocatalysts can effectively boost catalytic activity with a low overpotential. More importantly, by placing a single particle on a nanoelectrode, structural changes during electrocatalysis can be directly evaluated, providing in‐depth understanding for the catalyst's excellent OER performance.